Fostering oral interaction skills while using board games in an efl classroom. (2021)
The present research is an Exploratory Action Research that aims at developing a contextualized proposal for eleven-grade students from IED Colegio Sorrento in an English as Foreign Language Classroom (EFL). The proposal arises from the analysis of the diagnostic test and the students' difficulties. Based on these results, it is intended to promote their Oral Interaction Skills by using Board Games in the student’s learning process through the Game-Based Learning Approach. Additionally, there are some recommendations regarding the application of the activities and the material proposed.